12x+4=3(4-2)

Simple and best practice solution for 12x+4=3(4-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x+4=3(4-2) equation:


Simplifying
12x + 4 = 3(4 + -2)

Reorder the terms:
4 + 12x = 3(4 + -2)

Combine like terms: 4 + -2 = 2
4 + 12x = 3(2)

Multiply 3 * 2
4 + 12x = 6

Solving
4 + 12x = 6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + 12x = 6 + -4

Combine like terms: 4 + -4 = 0
0 + 12x = 6 + -4
12x = 6 + -4

Combine like terms: 6 + -4 = 2
12x = 2

Divide each side by '12'.
x = 0.1666666667

Simplifying
x = 0.1666666667

See similar equations:

| 3(7x-6)=5(2+5x) | | 96=-16t^2+120t+96 | | 3(2x-5)+x=6 | | 8x-9=2x+27 | | -5(a-1)+2(3a+4)=10a-3(2a+5) | | -18y^2-9y+5=0 | | T*8=46 | | 1.5xX-2.5=3.5xX+13.7 | | Z*9=54 | | 9(v-4)=3v+18 | | 6(v-2)-8v=-4 | | 4(6z-1)-3(z+4)=16(z+1) | | N=0.04x-79.06 | | (x+1)(x^3+7x^2+5x+4)= | | 10t=-22 | | x-27=-26 | | -3(4y-5)+2(2y+6)= | | 20a^2b^2-5a^4b^4= | | -3(t-9)-(t+7)=9 | | -4(x+6)= | | 6+5y=17 | | 22x-11=(x+5)(x+5) | | 3[2x-3(7x+y)]= | | 4a+5b=-6 | | -3x-1+7x+3= | | -y=60 | | (x-1)(x-1)=7x | | 5m=9 | | 2x+3=10x+21 | | ln(7x-13)=5 | | T*9=81 | | 13x+9-3=12x-2 |

Equations solver categories